The Upper Semicontinuity of Random Attractor for Stochastic Suspension Bridge Equation (Journal of Nonlinear Modeling and Analysis, 2024)
Based on the existence of pullback attractors for stochastic suspension bridge in [7], in the paper, we further investigate the upper semicontinuityof pullback attractors for the problem.
Keywords: Upper semicontinuity; Suspension bridge equations; Random attractors; Linear memory; Additive noise.